Training caretakers to clean community wells is a highly cost-effective way to reduce exposure to coliform bacteria - Md. Ahasan Habib; Serena Cocciolo; Md. Mir Abu Raihan; Prosun Bhattacharya; Anna Tompsett (npj Clean Water)
Abstract Existing strategies for improving global access to safe drinking water have met only limited success. We consider an unglamorous and often neglected dimension of drinking water infrastructure provision: cleaning. We randomly assigned caretakers of community wells to participate in a training workshop about how to clean wells. Thirteen to seventeen months later, wells with caretakers assigned to receive training have negligible rates of contamination with Escherichia coli (13 months: 2%; 17 months: 4%), while control wells have substantial rates of E. coli contamination (13 months: 14%; 17 months: 19%). Rates of contamination with any coliform bacteria are almost halved (13 months: control 55%, treated 30%; 17 months: control 77%, treated 46%). We estimate the cost of preventing exposure to coliform bacteria in drinking water to be US$0.89 per person and that, if scaled up, each US$2376 spent on the intervention could avoid the death of a child.